2012
DOI: 10.1161/circulationaha.111.063644
|View full text |Cite|
|
Sign up to set email alerts
|

Randomized Comparison of Everolimus-Eluting and Sirolimus-Eluting Stents in Patients Treated With Percutaneous Coronary Intervention

Abstract: for the Scandinavian Organization for Randomized Trials With Clinical Outcome IV (SORT OUT IV) InvestigatorsBackground-Among drug-eluting stents released to date, the sirolimus-eluting stent has demonstrated the least amount of late lumen loss, but its efficacy and safety have not been compared head-to-head with the next-generation everolimus-eluting stent. Methods and Results-The Scandinavian Organization for Randomized Trials with Clinical Outcome IV (SORT OUT IV)trial was a randomized multicenter, single-bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 146 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…This difference can be explained partly by the procedure-related myocardial infarction, which was not part of the primary end point in the SORT OUT VII trial, and by the slightly higher clinically indicated target lesion revascularization rate in the BIOSCIENCE trial. The SORT OUT VII trial, such as the previous SORT OUT trials, 7,17,25,27 relied on registry-based event detection without study-related angiographic or clinical follow-up. Patient care complied with standard clinical practice (hospital outpatient visit after 1-3 months).…”
Section: Downloaded From Sirolimus-eluting Vs Biolimus-eluting Biodegmentioning
confidence: 99%
“…This difference can be explained partly by the procedure-related myocardial infarction, which was not part of the primary end point in the SORT OUT VII trial, and by the slightly higher clinically indicated target lesion revascularization rate in the BIOSCIENCE trial. The SORT OUT VII trial, such as the previous SORT OUT trials, 7,17,25,27 relied on registry-based event detection without study-related angiographic or clinical follow-up. Patient care complied with standard clinical practice (hospital outpatient visit after 1-3 months).…”
Section: Downloaded From Sirolimus-eluting Vs Biolimus-eluting Biodegmentioning
confidence: 99%
“…According to statistical data published by the World Health Organization (WHO) in 2012, the number of the people dying from CVDs is expected to increase from 17 million in 2008 to 25 million in 20301. With the wide application and rapid development of micro-traumatic intervention treatment, the implantation of vascular stents is acknowledged to be one of the most effective approaches for CVDs234.…”
mentioning
confidence: 99%
“…In the BASKET-PROVE (BAsel Stent Kosten Effektivitäts Trial PROspective Validation Examination) study, SES and EES showed similar composite endpoints and stent thrombosis rates at 24 months 66. The SORT OUT IV trial showed noninferiority of the EES platform with regards to a composite clinical endpoint of safety (cardiac death, MI, and stent thrombosis) and efficacy, ie, target vessel revascularization (hazard ratio 0.94; 95% CI [0.67–1.31], P =0.71) 67. At 18 months, the EES continued to show noninferiority, with significantly lower rates of stent thrombosis (0.2% versus 0.9%, P =0.02) 67.…”
Section: Stent Evolution In Clinical Trialsmentioning
confidence: 92%
“…The SORT OUT IV trial showed noninferiority of the EES platform with regards to a composite clinical endpoint of safety (cardiac death, MI, and stent thrombosis) and efficacy, ie, target vessel revascularization (hazard ratio 0.94; 95% CI [0.67–1.31], P =0.71) 67. At 18 months, the EES continued to show noninferiority, with significantly lower rates of stent thrombosis (0.2% versus 0.9%, P =0.02) 67. These data suggest that the EES platform has improved safety and efficacy over the first-generation SES.…”
Section: Stent Evolution In Clinical Trialsmentioning
confidence: 99%